Analisis Potensi Hijauan Bahan Pakan Ternak Ruminansia di Desa Sukawening Kecamatan Dramaga Kabupaten Bogor Jawa Barat - Elsi Ramadhani; Agik Suprayogi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Potential land and pasture fields are very abundant especially in Sukawening Village. But the maintenance system is still extensive-traditional, which is grazing in natural pastures, between or under plantation crops (coconut, banana) where livestock are left free to graze, while some animals are tethered, this is one of the obstacles to increasing productivity of ruminants. Analysis of the potential forage of feed ingredients is very well carried out to support the realization of animal husbandry systems and feeding management. Bogor Agricultural Institute incorporated in the Six University Initiatie Japan Indonesia Service Learning Program sent 17 students to study with the community in Sukawening Village, Dramaga District, Bogor Regency. Students observe and participate directly in participating and assisting community activities during the program and analyzing the development of forage potential through service and learning programs. Analysis of the potential forage of feed ingredients can be used as inventory data of forage types that can be utilized to make efficiency of the quality and quantity of animal feed. Keywords: animal feed, community-based development, forage